Filling-coating synergistic modified polytetrafluoroethylene and preparation method thereof
By using carbonaceous reinforcement materials as filler materials in the polytetrafluoroethylene composite material and depositing a hydrogen-containing amorphous carbon-based coating and amorphous carbon-based coating containing metal elements on its surface to form a dual-structure coating, the problem of insufficient wear resistance of the polytetrafluoroethylene composite material is solved, and higher wear resistance and surface hardness are achieved.
Patent Information
- Application Number
- CN202510071960.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-16
- Publication Date
- 2025-04-15
AI Technical Summary
The prior art is difficult to effectively improve the wear resistance of polytetrafluoroethylene composite materials, and the effect of modification of a single fill material or surface coating is limited.
Using fill-coat collaborative modification technology, a dual-structure coating is formed to improve the wear resistance of the material by adding carbonaceous reinforcement material to the polytetrafluoroethylene composite material as the filling material, and depositing a hydrogen-containing amorphous carbon-based coating and amorphous carbon-based coating with metal elements on its surface.
The better wear resistance and surface hardness of the polytetrafluoroethylene composite material is achieved, the friction coefficient and wear amount are reduced, and the wear performance of the material is significantly improved.
Smart Images

Figure CN119823513A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to polytetrafluoroethylene and a preparation method thereof, in particular to filling-coating synergistically modified polytetrafluoroethylene and a preparation method thereof. Background Art
[0002] Polytetrafluoroethylene is widely used as a modern engineering lubricant due to its excellent chemical stability, hydrophobicity, tribological properties, etc., and is used as a sealing material in the sealing structure of aerospace hydraulic systems. The carbon-fluorine bond in polytetrafluoroethylene has extremely high stability. The fluorine atoms completely cover the carbon chain due to their high electronegativity, providing chemical inertness and extremely low surface energy, which gives it good self-lubricating properties. This characteristic also causes the polytetrafluoroethylene molecular chain to rely solely on van der Waals forces to maintain, and the bonding strength between the molecular chains is insufficient, resulting in a large amount of material wear and peeling during service. Realizing polytetrafluoroethylene composite materials with low friction and low wear properties has always been a hot topic and a difficult problem in the sealing field.
[0003] Surface coating modification technology can change the surface properties of the substrate (polytetrafluoroethylene) without affecting the internal structure and properties of the material, and can effectively improve the tribological properties of the material through a suitable self-lubricating coating; however, due to the high chemical inertness of polytetrafluoroethylene, surface coating modification technology has little effect on improving the wear resistance of polytetrafluoroethylene. Filler material modification is the main means to enhance the wear resistance of polytetrafluoroethylene. The modification of micron-level hard filler materials can effectively improve the interface contact state of polytetrafluoroethylene composites during the friction process, inhibit the crack propagation on the surface and subsurface of polytetrafluoroethylene through the effective support of the filler, and reduce the shear strength of the interface. In the prior art, the method for improving the wear resistance of polytetrafluoroethylene is single, and the effect of improving the wear resistance of polytetrafluoroethylene is poor. Summary of the invention
[0004] The purpose of the present invention is to provide a filling-coating synergistic modified polytetrafluoroethylene and a preparation method thereof, so as to further improve the wear resistance of the polytetrafluoroethylene composite material.
[0005] The technical solution adopted by the present invention is as follows: A filling-coating synergistically modified polytetrafluoroethylene, characterized in that its raw materials include polytetrafluoroethylene, a filling material, an amorphous carbon-based material containing H, and an amorphous carbon-based material containing H and at least one metal of Ti, Cr, Co, Ni, W, and Zr.
[0006] Preferably, the filling material is a carbonaceous reinforcing material; the filling material includes: at least one of carbon fiber, graphene, carbon nanotube, and fullerene; the mass ratio of the filling material is 1 wt%-20 wt%.
[0007] A method for preparing filling-coating synergistically modified polytetrafluoroethylene, characterized by comprising the following steps: (1) Put polytetrafluoroethylene and filler materials into a mixer and mix them evenly to prepare a preliminary mixed material; (2) uniformly mixing the preliminary mixed material with anhydrous ethanol to obtain a mixed material; (3) drying the mixed materials at 60-120° C. to obtain a polytetrafluoroethylene composite material; (4) pressing the polytetrafluoroethylene composite material through a mold to obtain a semi-finished blank, placing the semi-finished blank into a sintering furnace for sintering, and obtaining a polytetrafluoroethylene composite material substrate; (5) After grinding the polytetrafluoroethylene composite material substrate with sandpaper, polishing the polytetrafluoroethylene composite material substrate with a polishing machine, and finally cleaning the polished polytetrafluoroethylene composite material substrate with anhydrous ethanol; (6) installing a carbon target and at least one metal target of Ti, Cr, Co, Ni, W, and Zr at different target installation positions of the magnetron sputtering equipment; (7) placing a polytetrafluoroethylene composite material substrate on a sample stage in a chamber of a magnetron sputtering device, evacuating the chamber of the magnetron sputtering device, raising the temperature, introducing argon gas into the chamber of the magnetron sputtering device, setting the ion beam power supply voltage to 1000 V, applying a pulse bias voltage to the polytetrafluoroethylene composite material substrate, and obtaining a plasma pretreated substrate; (8) introducing argon gas and acetylene gas into the chamber of the magnetron sputtering equipment, and supplying current to the carbon target in the magnetron sputtering equipment for 5-20 minutes to deposit an amorphous carbon-based coating containing H; (9) Supplying electric current to the carbon target and the metal target in the magnetron sputtering device simultaneously for 90-180 minutes to deposit an amorphous carbon-based coating containing H and at least one metal selected from the group consisting of Ti, Cr, Co, Ni, W, and Zr; and forming a low-density amorphous carbon-based coating based on polytetrafluoroethylene and a high-density amorphous carbon-based coating based on a filler material.
[0008] Preferably, the total thickness of the H-containing amorphous carbon-based coating and the amorphous carbon-based coating containing H and at least one metal selected from Ti, Cr, Co, Ni, W, and Zr described in the present invention is 80 nm to 200 nm.
[0009] Preferably, in step (1), the mass ratio of polytetrafluoroethylene to the filling material is 9-4:1.
[0010] Preferably, the mass ratio of the mixed ingredients to anhydrous ethanol in step (2) is 1:1-2.
[0011] Preferably, the sintering process in step (4) is as follows: heating to 327°C at 0.8-1.2°C / min, keeping warm for 30-90min, heating to 375°C at 0.8-1.2°C / min, keeping warm for 60-120min, cooling to 327°C within 90-150min, keeping warm for 30-90min, cooling to 220°C within 200-330min, keeping warm for 30-90min, and finally naturally cooling to room temperature.
[0012] Preferably, the polishing machine in step (5) has a rotation speed of 600-800 r / min.
[0013] Preferably, the chamber of step (7) is heated to 80-120 degrees Celsius, and an argon gas flow is introduced at a rate of 30-50 sccm per cubic meter, which is determined according to the volume of the chamber; and the applied pulse bias voltage is -300 V to -500 V.
[0014] Preferably, in step (8), the argon and acetylene gas flows introduced into the chamber are 30-40 sccm and 5-10 sccm per cubic meter respectively, the applied pulse bias is -100 to -200 V, and the carbon target current is 1-2 A.
[0015] Preferably, in step (9), the current provided to the metal target is 0.2-0.4 A.
[0016] The invention provides a highly wear-resistant filling-coating synergistic modified polytetrafluoroethylene and a preparation method thereof, which has the following advantages over the prior art: The synergistically modified polytetrafluoroethylene prepared by the present invention can realize a double-structure coating on the surface of the substrate by synergistically modifying the filling modification and the surface modification: a low-density amorphous carbon-based coating with polytetrafluoroethylene as the substrate and a high-density amorphous carbon-based coating with carbon reinforcement materials such as carbon fibers as the substrate. The low-density amorphous carbon-based coating with polytetrafluoroethylene as the substrate has a lower hardness, can effectively achieve coordinated deformation with the substrate, and reduce the contact between the substrate and the grinding pair. The node-type distribution structure composed of carbon reinforcement materials such as carbon fibers and amorphous carbon-based coatings with high density, high hardness and high self-lubricating properties has the dual characteristics of interface load support and self-lubrication. The node-type distribution form of the high-hardness amorphous carbon-based coating also effectively avoids the deterioration of tribological properties caused by the inconsistent coordinated deformation ability between the substrate and the coating. The synergistic effect of the dual structure enables the polytetrafluoroethylene composite material to have more excellent wear resistance and surface hardness. The present invention can greatly improve the wear performance of the polytetrafluoroethylene composite material and reduce its friction coefficient. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 Schematic diagram of the structure of filling-coating synergistically modified polytetrafluoroethylene In the figure, 1. polytetrafluoroethylene, 2. carbonaceous filling material, 3. amorphous carbon-based coating containing H, 4. low-density amorphous carbon-based coating containing H and metal elements (based on polytetrafluoroethylene), 5. high-density amorphous carbon-based coating containing H and metal elements (based on carbonaceous reinforcing materials such as carbon fibers).
[0018] Figure 2 This is the Raman spectrum result of the surface coating structure of Example 2.
[0019] In the figure, the curve in the upper part is the Raman spectrum of the amorphous carbon-based coating containing H and metal elements at low density and its fitting curve, and the curve in the lower part is the Raman spectrum of the amorphous carbon-based coating containing H and metal elements at high density and its fitting curve. D / I G is the ratio of the D peak intensity to the G peak intensity obtained by Gaussian fitting of the Raman spectrum curve. D / I G Represents the sp in amorphous carbon-based coatings 2 The proportion of hybridized carbon atoms is high (low density).
[0020] Figure 3 This is a graph of average friction coefficient and wear rate of the filled-coated modified polytetrafluoroethylene and the carbon fiber filled modified polytetrafluoroethylene of Example 2. DETAILED DESCRIPTION
[0021] The preparation and performance of the filling-coating synergistic modified polytetrafluoroethylene of the present invention are further described below through specific examples, but are not intended to limit the patent of the present invention.
[0022] A filling-coating synergistic modified polytetrafluoroethylene, the specific structure is shown in the attached Figure 1 The raw materials include polytetrafluoroethylene, filler material, amorphous carbon-based material containing H, and amorphous carbon-based material containing H and at least one metal selected from Ti, Cr, Co, Ni, W, and Zr. The filler material is a carbonaceous reinforcing material, including at least one selected from carbon fiber, graphene, carbon nanotube, and fullerene; the mass ratio of the filler material is 1 wt%-20 wt%. The substrate is composed of polytetrafluoroethylene and filler material, and the coating is composed of an amorphous carbon coating containing H and an amorphous carbon-based coating containing H and metal elements.
[0023] Example 1 A preparation method of filling-coating synergistically modified polytetrafluoroethylene: (1) Step S1: Place polytetrafluoroethylene powder and carbon nanotubes in a mixer at a mass ratio of 4:1 and mix for 10 minutes to prepare a preliminary mixed material.
[0024] (2) Step S2: The preliminary mixed material and anhydrous ethanol are mixed in a mass ratio of 1:1, stirred at 25° C. for 2 h, and then stirred with ultrasonic waves for 2 h to achieve complete mixing, thereby obtaining a mixed material; (3) Step S3: drying the mixed material at 100° C. for 24 h to obtain a polytetrafluoroethylene composite material; (4) Step S4: The polytetrafluoroethylene composite material is pressed by cold compression (40 Mpa, 30 min) to obtain a semi-finished blank, and the semi-finished blank is placed in a muffle furnace for sintering to obtain a polytetrafluoroethylene composite substrate. Sintering process: heating to 327°C at 1°C / min, keeping warm for 60 min, heating to 375°C at 1°C / min, keeping warm for 90 min, cooling to 327°C within 120 min, keeping warm for 60 min, cooling to 220°C within 267 min, keeping warm for 60 min, and finally cooling naturally to room temperature.
[0025] (5) Step S5: polishing the polytetrafluoroethylene composite material substrate using sandpaper of 1000, 1200, 1500 and 2000 meshes in sequence, polishing the polytetrafluoroethylene composite material substrate using a polishing machine at a speed of 600 r / min, and cleaning the polished polytetrafluoroethylene composite material substrate with anhydrous ethanol; obtaining a filled modified polytetrafluoroethylene (polytetrafluoroethylene composite material substrate).
[0026] (6) Step S6: installing a carbon target (graphite) and a Cr metal target at different target installation positions of the magnetron sputtering equipment respectively; (7) Step S7: Place the polytetrafluoroethylene composite substrate on the sample stage in the chamber of the magnetron sputtering equipment, evacuate the chamber of the magnetron sputtering equipment, and increase the temperature. The pressure in the chamber is 5×10 -3 Pa, the temperature is 100° C.; argon gas with a purity of at least 99.999% is introduced into the chamber, the gas flow rate is 45 sccm, the ion beam power supply voltage is 1000 V, and a -500V pulse bias is applied to the substrate to obtain a plasma pretreated substrate; (8) Step S8: high-purity argon and acetylene gas were introduced into the chamber with gas flow rates of 34 sccm and 6 sccm, respectively, 2 A current was supplied to the carbon target and a -200 V pulse bias was applied to the substrate to deposit an amorphous carbon-based coating containing H for 5 min; (9) Step S9: The other parameters in step S8 remain unchanged, and a current of 0.4 A is supplied to the Cr metal target to deposit an amorphous carbon-based coating containing H and Cr for 90 min.
[0027] Example 2 A preparation method of filling-coating synergistically modified polytetrafluoroethylene: (1) Step S1: Mixing polytetrafluoroethylene powder and carbon fiber powder in a mass ratio of 4:1 in a mixer for 10 minutes to prepare a preliminary mixed material; (2) Step S2: Same as step S2 of the preparation method in Example 1.
[0028] (3) Step S3: Same as step S3 of the preparation method in Example 1.
[0029] (4) Step S4: the same as step S4 of the preparation method in Example 1.
[0030] (5) Step S5: Same as step S5 of the preparation method in Example 1.
[0031] (6) Step S6: installing a carbon target (graphite) and a Ti metal target at different target installation positions of the magnetron sputtering equipment respectively; (7) Step S7: Place the polytetrafluoroethylene composite substrate on the sample stage in the chamber of the magnetron sputtering equipment, evacuate the chamber of the magnetron sputtering equipment, and increase the temperature. The pressure in the chamber is 6×10 -3 Pa, temperature is 100 ° C; high-purity argon gas is introduced into the chamber, the gas flow rate is 40sccm, the ion beam power supply voltage is 1000 V, and a -400 V pulse bias is applied to the substrate to obtain a plasma pretreated substrate; high-purity argon gas refers to argon gas with a purity of at least 99.999%.
[0032] (8) Step S8: high-purity argon gas and acetylene gas were introduced into the chamber, with gas flow rates of 34 sccm and 6 sccm, respectively, a current of 1.5 A was supplied to the carbon target and a pulse bias of -150 V was applied to the substrate to deposit an amorphous carbon-based coating containing H for 10 min; (9) Step S9: The other parameters in step S8 remain unchanged, and a current of 0.3 A is supplied to the Ti metal target to deposit an amorphous carbon-based coating containing H and Ti for 110 min; thus, a filling-coating synergistically modified polytetrafluoroethylene is obtained.
[0033] The chamber capacity (spatial volume) of the magnetron sputtering equipment used in Example 1 and Example 2 is 1 cubic meter.
[0034] Performance characterization: The coating of the filling-coating synergistically modified polytetrafluoroethylene prepared in Example 2 was measured by a coating thickness tester, and the coating thickness was 110.2 nm; that is, the sum of the thicknesses of the amorphous carbon-based coating containing H and the amorphous carbon-based coating containing H and Ti was 110.2 nm.
[0035] The filler-coating synergistically modified polytetrafluoroethylene material prepared in Example 2 and the carbon fiber filled modified polytetrafluoroethylene composite material prepared in steps S1 to S5 of Example 2 were tested by a ball-on-disc friction and wear tester to obtain their friction coefficients (the friction pair was a GCr15 ball with a radius of 3 mm), and the wear rate was obtained by means of a white light interferometer; the results are as follows: Figure 3 The test results shown in the figure are as follows: the amorphous carbon-based coating structure of polytetrafluoroethylene and carbon fiber surface was obtained by Raman spectrometer. By comparing the tribological properties, it was found that compared with the polytetrafluoroethylene composite material modified by carbon fiber filled according to steps S1 to S5 of this embodiment, the wear loss of the polytetrafluoroethylene composite material modified by filling-coating synergistic modification was reduced by 51.09%, and the friction coefficient was reduced by 8.89%.
Claims
1. A filling-coating synergistically modified polytetrafluoroethylene, characterized in that: The raw materials include polytetrafluoroethylene, filler material, amorphous carbon-based material containing H, and amorphous carbon-based material containing H and at least one metal selected from the group consisting of Ti, Cr, Co, Ni, W and Zr.
2. The filling-coating synergistically modified polytetrafluoroethylene according to claim 1, characterized in that: The filling material is a carbonaceous reinforcing material; the filling material includes: at least one of carbon fiber, graphene, carbon nanotube, and fullerene.
3. A method for preparing filling-coating synergistically modified polytetrafluoroethylene, characterized in that: The following steps are involved: (1) Put polytetrafluoroethylene and filler materials into a mixer and mix them evenly to prepare a preliminary mixed material; (2) uniformly mixing the preliminary mixed material with anhydrous ethanol to obtain a mixed material; (3) drying the mixed materials at 60-120° C. to obtain a polytetrafluoroethylene composite material; (4) pressing the polytetrafluoroethylene composite material through a mold to obtain a semi-finished blank, placing the semi-finished blank into a sintering furnace for sintering, and obtaining a polytetrafluoroethylene composite material substrate; (5) After grinding the polytetrafluoroethylene composite material substrate with sandpaper, polishing the polytetrafluoroethylene composite material substrate with a polishing machine, and finally cleaning the polished polytetrafluoroethylene composite material substrate with anhydrous ethanol; (6) installing a carbon target and at least one metal target of Ti, Cr, Co, Ni, W, and Zr at different target installation positions of the magnetron sputtering equipment; (7) placing a polytetrafluoroethylene composite material substrate on a sample stage in a magnetron sputtering chamber, evacuating the chamber of the magnetron sputtering chamber, raising the temperature, introducing argon gas into the chamber of the magnetron sputtering chamber, setting the ion beam power supply voltage to 1000 V, applying a pulse bias to the polytetrafluoroethylene composite material substrate, and obtaining a plasma pretreated substrate; (8) introducing argon gas and acetylene gas into the chamber of the magnetron sputtering equipment, and supplying current to the carbon target in the magnetron sputtering equipment for 5-20 minutes to deposit an amorphous carbon-based coating containing H; (9) Supplying electric current to the carbon target and the metal target in the magnetron sputtering device simultaneously for 90-180 minutes to deposit an amorphous carbon-based coating containing H and at least one metal selected from the group consisting of Ti, Cr, Co, Ni, W, and Zr; and forming a low-density amorphous carbon-based coating based on polytetrafluoroethylene and a high-density amorphous carbon-based coating based on a filler material.
4. The method for preparing the filling-coating synergistically modified polytetrafluoroethylene according to claim 3, characterized in that: In step (1), the mass ratio of polytetrafluoroethylene to the filling material is 9-4:
1.
5. The method for preparing the filling-coating synergistically modified polytetrafluoroethylene according to claim 3, characterized in that: The sintering process described in step (4) is as follows: heating to 327°C at 0.8-1.2°C / min, keeping warm for 30-90 min, heating to 375°C at 0.8-1.2°C / min, keeping warm for 60-120 min, cooling to 327°C within 90-150 min, keeping warm for 30-90 min, cooling to 220°C within 200-330 min, keeping warm for 30-90 min, and finally cooling naturally to room temperature.
6. The method for preparing the filling-coating synergistically modified polytetrafluoroethylene according to claim 3, characterized in that: The polishing machine described in step (5) has a rotation speed of 600-800 r / min.
7. The method for preparing the filling-coating synergistically modified polytetrafluoroethylene according to claim 3, characterized in that: The chamber of step (7) is heated to 80-120 degrees Celsius, and an argon gas flow is introduced at a rate of 30-50 sccm per cubic meter, which is determined according to the volume of the chamber; the pulse bias voltage applied is -300 V to -500 V.
8. The method for preparing the filling-coating synergistically modified polytetrafluoroethylene according to claim 3, characterized in that: In step (8), the argon and acetylene gas flows into the chamber are 30-40 sccm and 5-10 sccm per cubic meter respectively, the applied pulse bias is -100 to -200 V, and the carbon target current is 1-2 A.
9. The method for preparing the filling-coating synergistically modified polytetrafluoroethylene according to claim 3, characterized in that: In step (9), the current provided to the metal target is 0.2-0.4 A.